Factors that motivate accounting students to pay zakat and sadaqah at Universitas Islam Indonesia (UII) - Fitriati Akmila; Khalla Okta Dega Laksana (Proceeding of National Conference on Accounting & Finance, 2021)
The purpose of this research is to analyze the effect of Zakat and Sadaqah Knowledge, Knowledge of Islamic Financial Literacy and Self-Awareness on student’s motivation in paying Zakat and Sadaqah. This study used primary data by sending online questionnaire to Accounting Students at FBE UII. The sampling used for this research was 100 students from Accounting departement  batch 2016-2019. Multiple Linear Regression is used for data analysis. The results of this study showed that Zakat and Sadaqah Knowledge has a positive impact on students motivation for paying them. Similarly, knowledge of Islamic financial literacy also has positive effect on students motivation of paying Zakat and Sadaqah. Lastly, self-awareness has positive effect on Students Motivation of paying Zakat and Sadaqah. These concluded that accounting students in Faculty Business and Economic UII has a high motivation to pay Zakat and Sadaqah and implementing them in their life.